Srategi Guru Bimbingan dan Konseling Menumbuhkan Karakter Jujur dan Bertanggung Jawab pada Siswa - Siagian, Muhammad Ravi; Tambusai, Khairuddin (Fitrah: Journal of Islamic Education, 2023)
This study aims to identify and analyze the strategies applied by guidance and counseling teachers at Madrasah Aliyah Laboratory of the State Islamic University of North Sumatra in fostering students' honest and responsible character. The method used in this study is a qualitative approach, based on phenomenological studies. Data collection techniques through interviews, observation, and documentation. The research sample included guidance and counseling teachers, students, and other support staff involved in the guidance and counseling process in schools. The results of the study show that students in class XI at the school already have a fairly high level of honest characteristics. The strategy used in forming honest and responsible characters is integrating values ​​and ethics in each subject, internalizing positive values ​​in students, providing habituation and training, and setting an example. In forming honest and responsible characters, the teacher applies three main stages, namely moral knowing (instilling moral knowledge), moral feeling (instilling a sense of love and being happy to do what is good and right), and moral action (carrying out moral actions that are supported by understanding and former love, which later becomes a habit.